Comparative Trend Analysis of Mustard in Bundelkhand Region, Uttar Pradesh and India - Kalia, Abhishek; Shukla, Gaurav; Mishra, Dheeraj; Mishra, Bhanu Prakash; Patel, Rajiv Ranjan (Indian Journal of Extension Education, 2021)
The study analyses time series data (1996 to 2019) on dynamics of area, production and productivity of mustard in India, Uttar Pradesh and Bundelkhand region. The growth trend analysis suggested that in India and U.P, area under mustard was decreasing with the compound growth rate of 0.2 and 2 per cent per annum respectively whereas it was increasing with compound growth rate of 4 per cent annually in Bundelkhand region. Growth trend analysis for production also indicated same pattern, CGR of India was found 1.5, -0.5 per cent for U.P but in Bundelkhand region it was found 8 per cent. The growth trend analysis for productivity indicated compound growth rate of 1.7 per cent per annum at country level, 1.6 per cent U.P. and 4.3 per cent in Bundelkhand region. The instability indicated the highest variability in area observed in Bundelkhand region with 23.23 per cent and lowest in Uttar Pradesh with 11.7 per cent, highest variability in production was observed in Bundelkhand region with 48.0 per cent and lowest in India with 14.8 per cent and highest variability in productivity was observed in Bundelkhand region with 25.2 per cent and lowest in Uttar Pradesh with 8.2 per cent. Productivity effect on production variability of mustard was found highest in Uttar Pradesh followed by India and Bundelkhand respectively.
Keywords: Area; Compound annual growth rate; Decomposition; Production